Atrazine dissipation in a biobed system inoculated with immobilized white-rot fungi. Issue 10 (2nd October 2016) - Elgueta, Sebastian; Santos, Cledir; Lima, Nelson; Diez, Maria Cristina
ABSTRACT: Due to environmental concerns about accumulation of the herbicide atrazine in food products and water reservoirs, there is a need to develop safe and economical methods for its dissipation. The main aim of this study was to evaluate atrazine dissipation in a biobed system inoculated with immobilized white-rot fungi in a pelletized support (PS). All fungal isolates evaluated were efficient in colonizing the surface and inner parts of the PS, with no differences observed in the colonization over the assay. The highest atrazine dissipation (93%) was observed for Stereum hirsutum Ru-104 after 60 days of incubation. In contrast, the lowest atrazine dissipation (78%) was observed for the non-inoculated biobed over an identical period. Trametes versicolor HL01 was involved in the highest phenoloxidase activity. This activity indicates that inoculated and non-inoculated biobeds were biologically active over the incubation period. A high respiration rate in the biobed was observed when it was inoculated with S. hirsutum Ru-104. Inoculation of fungi on PS systems may be a coadjutant in the increase of fungal efficiency in enzymatic production.